Торговельне місто Луцьк у XVI - першій половині XVII ст. - Штанько, Оксана; Shtanko, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2013)
У розвідці проаналізовано особливості розвитку міської торгівлі Луцька у ХVІ – першій половині ХVІІ ст. На підставі текстів князівсько-королівських привілеїв визначено правове підґрунтя організації торгівлі Лучеська на етапі рецепції й утвердження в місті магдебурзького права. На основі актових матеріалів віднайдено імена луцьких міщан, які займалися торгівлею, та їхні «професійні» спеціалізації.

The article analyzes peculiarities of the trade in Lutsk at the early New time. With help of texts of privileges by princes and king was defined legal basis of trading policy at the period of reception and consolidation in Lutsk rules of Magdeburg right. On the basis of documentary material discovered names of Lutsk citizens who were engaged in trade and their «professional» specializations. Luchesk, having the status of one of the main towns of Great kingdom of Lithuania, and later ‒ the Commonwealth, and settling at the crossroads of major trade routes of the country, was condemned to the successful development of trading. This process was facilitated by the best talent the city of Magdeburg rights and a number of accompanying privileges that expanded trade capacity of urban society and denied the payment ‒ fees and taxes, cash equivalent which, in turn, directed to improvement of the city.
Trading City Lutsk in 16 – First Half of 17-th Century
Keywords: Луцьк; торгівля; міщани; ярмарки; торги; Ринкова площа; Lutsk; trade; citizens; fairs; auctions; Market Square